Increase in the minimum wage in 2024: its effects and conditions in the Mexican labor market - Andrade Rosas, Luis Antonio; Chiatchoua, Cesaire (Revista Internacional de Salarios Dignos, 2023)
During the current administration, increases in the minimum wage have averaged 20%. On december 1, 2023, CONASAMI announced that the increase in the minimum wage will be 20% for 2024, the same as in 2023. Contrary to what COPARMEX estimated at 12% and within the limit that some analysts estimated between 15% and 20%. Based on estimates of labor supply and demand, this report presents the effects of this increase on the labor market. In particular, it is observed that the valuation of workers and subsidies by the government are key so that the 20% increase in the minimum wage does not have a considerable impact on the imbalances in the labor market.